Green Economy Financing According to Fiqh Al-Biah as Part of Maqashid Sharia - Mahmud Yusuf; Fathurrahman Azhari; Fahmi Al Amruzi; Muhammad Maulidi Ihsan Wahidi; Sri Anafarhanah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
Economic development in the 20th century had a huge impact on the sustainable development of mankind. On the other hand, however, it has a negative impact on living ecosystems. In many aspects such as the orientation of the interests of sustainable development, the economy and the environment are considered as two opposing aspects. Sustainable Development Based on this, a relatively new concept emerged, namely the green economy. The green economy is a concept that supports human well-being and cares about environmental and ecosystem sustainability in economic development. But on the negative side, economic development can also have an impact on the reduction of natural resources through over-exploitation, industrial pollution, oil, water, and air pollution due to flooding, and the impact on climate change. Islam has an ideal concept of sustainable development. At least there are fundamental rules for supporting sustainable development, namely the implementation of fiqh al-bi'ah based on maqashid sharia for the management of Islamic resources in the economy. Islam has an ideal concept of sustainable development. At least there are basic rules to support sustainable development, namely the application of fiqh al-bi'ah based on maqashid Sharia law to manage Islamic resources in the economy.